Moscow - Vorhees, Mara; Ragozin, Leonid (Footscray, Vic. : Lonely Planet Publications, 2015)
Swoon beneath the colorful onion domes and riotous design of beloved St Basil's Cathedral Step into Red Square and surround yourself with centuries of Russian politics and intrigue Sip a cocktail and contemplate Moscow's contemporary art while DJs spin tunes Discover the villages of yesteryear Russia amid the rolling countryside of the Golden Ring.
Previous ed.: 2012.
Pull-out map.
Includes index.
Keywords: Moscow (Russia); Russia (Federation) -- Moscow; Guidebooks